Value creation in multinational enterprise - Choi, J. Jay; Click, Reid William (International finance review ;, 2006)
The papers in this volume of International Finance Review provide a reflection on the role of international finance - and its relationship to strategy, economics, political science and public policy - in examining value creation in multinational enterprise. These are 22 original papers submitted specifically for this volume based on its theme. The papers present a breadth of methodologies, including theoretical, empirical, conceptual, and case study approaches. Several papers offer combinations of these different categories. Among the empirical papers, there are many kinds of data sets analyzed, ranging from macroeconomic data to firm-level financial data to survey data. In addition, the data sets are rigorously analyzed in many different ways. This volume also takes a broad perspective on multinational enterprise, which allows discussion of traditional areas in the study of multinational enterprises (MNEs) as corporations, but also includes topics related to multinational enterprise as an undertaking, not just as corporation. For example, there is attention to small and medium-sized companies as well as larger MNEs. There are also papers that consider exporting enterprises and the environment of multinational enterprise. With this spirit, the volume covers multinational enterprise from a variety of perspectives, including views from private corporations and government policymakers, and the authors of the papers include both academics and practitioners. Altogether, the papers offer insights into value creation through a variety of lenses.